What message are we sending bottle-feeding families when we place formula in the same retail category as cigarettes? - Moriarty, Clare (Image Magazine, 2021)
I have a powerful memory of first reflecting on Irish breastfeeding politics. I was 20 and visiting a then- new American coffee chain that had arrived on my local main street. Amid trying to figure out which series of words they wanted me to say to produce what was erstwhile obtainable as a “large black coffee” I noticed something unusual about the setting: the café had a disproportionate number of tables filled with women with babies. It was middayish and perhaps some kind of class had just finished nearby. At one table of four, two women were in different stages of openly breastfeeding babies and chatting. Initially—in line with my Irishness—I looked away, embarrassed by the possibility of a tiny amount of nudity. And then, thinking about how nice it was that Ireland—the Ireland of the Magdalene laundries, Mother and Baby homes and no divorce until the mid-1990s—had, at least in this leafy suburb, reached a place where some women felt at peace having a breast, or part of a breast, out at work in public. I thought about what a marker of spiritual growth this represented for the country and did my best to offer what I’m sure was an awkward and possibly creepy “good on you” smile in their general direction. I say all of this to say that I think that it’s wonderful that we have come to a place where breastfeeding in public can be a more relaxed part of family life. We have National Breastfeeding Week, an annual ‘Latching On’ ceremony, Breastival, and increasingly, parental leave contracts include special provisions to support breastfeeding women returning to work. I don’t doubt that we still have far to go, and that many still face difficult choices and anxiety in their infants’ journeys to solid food, but I’m hopeful that the promised land on that front is much closer than it has ever been, and, is approaching with ever-greater haste. These improvements for breastfeeding parents have not sprung from nowhere. Governing bodies at various levels have implemented policies aimed at increasing national breastfeeding figures because Ireland’s rates are low when compared with socioeconomically similar countries. This push towards breastfeeding has, in my view, had some negative consequences for people who formula feed. This article is about what I perceive to be a radical dogma that has emerged in Ireland. Having read what I can only describe as a bizarre and frustrating characterisation of the current situation by Sabina Higgins, as a research academic, I feel somewhat compelled to say a few words about some of this mythos. I am also a new mother, at great peace with a choice I made early on about feeding my daughter, and frequently flabbergasted by the rhetoric I find in the literature and advice on feeding infants. So, I try to do two things below: 1) make the case that the public rhetoric around feeding babies is often extreme and misleading, and 2) I discuss my own motivations in deciding to formula feed.
Image Magazine
Keywords: Breastfeeding; Breastfeeding Support; Parenthood